The Effect of Boattail Angles on the Near-Wake Structure of Axisymmetric Afterbody Models at Low-Speed Condition - The Hung Tran (International Journal of Aerospace Engineering)
The effect of a boattail angle on the structure of the wake of an axisymmetric model was investigated at low-speed condition. Four conical boattail models with angles of 0° (blunt-based body), 10°, 16°, and 22° were selected for this study. The Reynolds number based on the diameter of the model was around 1.97×104. Particle image velocimetry (PIV) was used to measure the velocity of the wake flow. The time-averaged flow characteristics including the length of recirculation of the afterbody, turbulent intensity, and Reynolds shear stress were analyzed and compared among those boattail models. The experimental results showed that the length of recirculation decreases with increasing boattail angle to 16°. At a boattail angle above 16°, the flow was fully separated near the shoulder and near-wake structure was highly changed. The turbulent intensity at a boattail angle of 22° showed a similar level to that in the case of the blunt-based body. Flow behavior on boattail surface should be accounted as an important parameter affecting the wake width and drag of the model. Power spectral density and proper orthogonal decomposition (POD) analyses showed that a Strouhal number of StD=0.2 dominated for the boattail model up to 16°. The fully separated flow was dominated by a Strouhal number of StD=0.03−0.06, which was firstly presented in this study.